CEGAH STUNTING DENGAN BEBAS ANEMIA PADA REMAJA DI SMPN 3 BANJARBARU KECAMATAN CEMPAKA KOTA BANJARBARU - Oktiyani, Neni; Norsiah, Wahdah; Thuraidah, Anny (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
Stunting is a condition where a child's height is shorter than the appropriate height for their age, which is caused by various factors, especially nutritional intake in the First 1000 Days of Life (HPK). Stunting has a negative impact on children's health and can hamper Indonesia's demographic bonus in the future. To prevent stunting, mothers need to get adequate nutritional intake during pregnancy and breastfeeding. However, preventing stunting must start from adolescence, because the impact of poor nutrition begins preconception. Previous research showed that 65% of female students at SMPN 3 Banjarbaru experienced anemia with hemoglobin (Hb) levels below normal. Therefore, education is needed to increase teenagers' knowledge in dealing with anemia in order to prevent stunting. This community service aims to empower active female students in the Youth Red Cross (PMR) and UKS as CAEM (Prevent Anemia) and Santun (Healthy Anti-Stunting) cadres. This activity is carried out through three stages: planning, implementation, and evaluation. The evaluation results showed that 79% of female students had normal Hb levels and 100% eosinophils within normal limits. The output of this activity includes the formation of youth cadres, increasing knowledge and skills, and improving the health of partners. Apart from that, there is cooperation between the Banjarmasin Ministry of Health Polytechnic and the fostered partners in the form of a Cooperation Agreement (PKS). All achievement targets for this activity were achieved, and it is recommended to involve teenage parents and experts in the field of Midwifery and Nutrition in further service activities.